Teknik dan Ideologi Penerjemahan Pada Puisi Terjemahan ‘Huesca’ Karya Chairil Anwar - Amar, Noezafri (Jurnal Penerjemahan, 2018)
This research is aimed at describing the techniques and ideology applied by Chairil Anwar in translating words, phrases, and clauses of John Cornford’s To Margot Heinemann poem into his Huesca translated poem. Thus, the researcher used the following procedures: 1) determining the data sources, data, and translation units to be analyzed; 2) determining the problems and aims of the research; 3) comparing the source text and translated text to identify the techniques that are applied; 4) describing the frequency of overall translation techniques found in the translated poem; 5) calculating the percentage of overall translation technique orientation to determine the translation ideology; 6) drawing the conclusion and proposing suggestion of research. The research shows that 1) Chairil Anwar just applied seven translation techniques i.e. adaptation, amplification, discursive creation, literal, modulation, reduction, and transposition; 2) based on the described frequency, it was found that the seven translation techniques were applied 42 times; 3) there is only one source text oriented - translation technique (foreignizing ideology) namely literal whereas the other six techniques are target language oriented (domesticating ideology); 4) based on the percentage of the seven translation techniques implementation, it was found that the foreignizing ideology was applied 17 times or 40,4% meanwhile the domesticating ideology were applied 25 times or 49,6%. Therefore, the ideology of Huesca poem tends to be domesticating. Finally, it can be concluded that Chairil Anwar’s good quality translated poem was a result of his implementation of quite varied translation techniques with a domesticating ideology tendency. Keywords: Translation techniques, foreignizing ideology, domesticating ideology, source text, Huesca poem.